PROBLEM-BASED LEARNING(PBL) MODEL IN ENHANCING STUDENTS' MOTIVATION AND LEARNING OUTCOMES IN TAX ADMINISTRATION - Eryani, Rossyda; Muchson, M.; Anas, M. (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study aims to improve student learning outcomes and mastery in Tax Administration through the application of a contextual learning approach, specifically Problem-Based Learning (PBL). A quantitative research method utilizing SPSS analysis was conducted on 106 students from class XII Akl at SMKN 2 Kota Blitar for the 2020/2021 academic year, selected using a saturated sample technique. The results indicate that students' learning motivation plays a crucial role before the implementation of the PBL model, influencing their readiness to face this new method. Additionally, there is a reciprocal relationship between learning motivation and student outcomes within the PBL context. This research highlights the importance of contextual approaches like PBL in enhancing students' understanding and application of tax concepts in real-world contexts, which are highly valuable skills for preparing students for careers in tax administration